APLIKASI KITOSAN TERADIASI SINAR GAMMA 50 kGRAY DALAM FORMULASI SEDIAAN NANOPARTIKEL GAMAVUTON-0 SECARA GELASI IONIK DENGAN PENGAIT SILANG TRIPOLIFOSFAT - , PUTRI ERDISA JANUARTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Chitosan is an ideal polymer for nanoparticle formulation. However, it has inconsistent physicochemical character and high molecular weight which result in poor solubility. Gamma irradiation is used to standardize the character of chitosan because it can induce chain scission in polymer. Gamavuton-0 (GVT-0) is the drug model used in this study because it has potential as anticancer agent but it has poor bioavailability due to its insoluble character, therefore it needs alternative for drug delivery with nanoparticle. In this study, local chitosan is irradiated with Gamma ray 50 kGray from Cobalt-60 by Badan Tenaga Atom Nasional (BATAN). Irradiated chitosan is characterized by its deacetylation degree and viscosity, and formulated with GVT- 0 to be nanoparticle using ionic gelation method and sodium tripolyphosphate (TPP) as crosslinking agent. Nanoparticle with stable formula is characterized by its morphology, particle size, polydispersity index, zeta potential, and entrapment efficiency. The characterization result is compared with nanoparticle formulated with non-irradiated chitosan. Gamma irradiated chitosan has more intense brown color, lower viscosity with 6,19 Â± 0,17 centiPoise, and higher deacetylation degree with 64,66%. The stable formula for nanoparticle formulation is 0,02% GVT-0